SISTEM LOGISTIK PERTANIAN ANTAR PULAU DARI PELABUHAN MANADO - Abram Tombey Kandou; Caroline B. D. Pakasi; Noortje ., Benu (AGRI-SOSIOEKONOMI, 2017)
The purpose of this study was to identify the existing agricultural logistics system in Manado Harbor. This research was conducted at Manado Port as the starting point and end point. The research conducted from February to May 2017. This research used primary and secondary data. Primary data is collected with a list of questions that have been prepared for Head of Port Authority Unit of Manado City Transportation Department. Secondary data are obtained, among others, from the Office of Transportation and Marine Guard Unity. Sampling was conducted using Snowball Sampling Technique. The variables that will be measured in the research of this result are: What agricultural logistics goods are held in the Port, How to store goods in Manado Port warehouse, What transportation is used for shipping agricultural logistics, How to distribution of agricultural logistics goods, How to service delivery, What is the distance between islands (km). This research uses descriptive analysis that is to identify inter-island agricultural logistic system from Manado port and map agricultural logistic system in Manado Port. The results show that the existing logistics system in Manado Harbor has decreased not too drastically and the increase is very drastic in the year 2015. And passenger flow in the year 2011-2013 is still normal, but in 2014 and 2015 experienced a drastic increase due to passengers who soaring in that year. Logistics system in Port Manado also can be categorized pretty good because the data collection is good but still not specified agricultural goods are loaded, and for the equipment can be said to be good seen in terms of Port Manado which is still included in the category of Passenger Port, ships anchored in the Port of Manado is quite a lot and will be added over time, due to the soaring passengers between islands and goods brought. And in terms of facilities for passengers Manado Port has been very good, because the construction of infrastructure for passengers is being carried out at the time of research and development results are already visible at the time this study is completed.